Relationship between levels of depression and academic performance in pre-university students, from regular cycle of 2015-1 in a National University of Metropolitan Lima - Chávez, Hilda (2017)
The development of applied, descriptive, correlational and transectional research was considered. The study population consisted of students enrolled in the 2015-I Ordinary Cycle of a University of Lima (from different regions of the country and graduates from both state and private educational institutions). They were used as instruments to collect data, the HAD test and the academic results obtained in the exams. For the data processing, descriptive and inferential statistics were used, using MS Excel and SPSS version 21. In the relationship between the diagnosis of anxiety and depression with academic performance, it was found that the greatest number of students were diagnosed as depression Normal and normal anxiety with an average academic performance of 757.22 points (equivalent in scale vigesimal to 07.57). It was found that the best average academic performance is in the area of Basic Sciences, with 809.85 points, while the lowest average academic performance corresponds to the area of Social Sciences, with 671.58 points. In Area E, which corresponds to Engineering, it brings together the largest number of students diagnosed with anxiety and depression. It is observed that in all the professional areas, the lowest academic performance is in the course of Algebra; While the highest academic achievement is in the courses of Universal History (areas D, E and A respectively) and Philosophy (areas B and C respectively). The obtained results allow to see the relationship between the variables, but also to apply the counseling and / or psychological tutoring to improve the academic task of the pre-university student.